2023
DOI: 10.1002/pon.6110
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta‐analysis of psychosocial interventions for immigrant and limited English proficient cancer patients

Abstract: Objective Immigrants, particularly those who are less acculturated and limited English proficient (LEP), often lack access to culturally and linguistically appropriate psychosocial care in cancer survivorship. We sought to determine what psychosocial interventions are available for immigrant and/or LEP cancer patients and to assess treatment and patient factors that may correlate with better psychosocial outcomes for this population. Methods We conducted a systematic review and meta‐analysis of studies publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 127 publications
(1,206 reference statements)
0
1
0
Order By: Relevance
“…These effects were generally maintained when compared with the experimental and control groups, with a few exceptions. These findings are consistent with other SLRs that investigated interventions to improve the psychosocial well-being of immigrant people using psychosocial variables such as reduction of stress, depression, anxiety, suicidal ideation, and PTSD [47][48][49][50]. Furthermore, the therapies used in these studies were consistent with those that we found in our SLR, such as cognitive-behavioral techniques [47][48][49][50], counseling [49], psychoeducation [49,50], art therapy [49,50], mindfulness and relaxation [48,49], and group interpersonal theory [48,49].…”
Section: Effects Of Interventions On Pwe Of Immigrant Womensupporting
confidence: 90%
“…These effects were generally maintained when compared with the experimental and control groups, with a few exceptions. These findings are consistent with other SLRs that investigated interventions to improve the psychosocial well-being of immigrant people using psychosocial variables such as reduction of stress, depression, anxiety, suicidal ideation, and PTSD [47][48][49][50]. Furthermore, the therapies used in these studies were consistent with those that we found in our SLR, such as cognitive-behavioral techniques [47][48][49][50], counseling [49], psychoeducation [49,50], art therapy [49,50], mindfulness and relaxation [48,49], and group interpersonal theory [48,49].…”
Section: Effects Of Interventions On Pwe Of Immigrant Womensupporting
confidence: 90%
“…Yet empirically supported mental health interventions developed for Chinese immigrants with advanced cancer are scarce. Our team's systematic review and meta-analysis of psychosocial interventions for immigrant and LEP cancer survivors identi ed only ve interventions that have been empirically tested for Chinese-speaking cancer patients [16][17][18][19], none of which were psychotherapy/counseling interventions [20]. There is a critical need to develop high-quality, culturally and linguistically tailored, and accessible mental health interventions for this growing yet underserved population [21].…”
Section: Introductionmentioning
confidence: 99%